Budding Uninhibited by Benzimidazole-1 Insufficiency Prevents Acute Renal Failure in Severe Sepsis by Maintaining Anticoagulant Functions of Vascular Endothelial Cells. Issue 3 (March 2019) - Matsubara, Yutaka; Matsumoto, Takuya; Yoshiya, Keiji; Yoshida, Ayae; Ikeda, Seiichi; Furuyama, Tadashi; Nakatsu, Yoshimichi; Tsuzuki, Teruhisa; Nomura, Masatoshi; Maehara, Yoshihiko
Abstract : ABSTRACT: Severe sepsis is critical to health and can result in acute renal failure (ARF). Tissue factor (TF) and thrombomodulin (TM) play key roles in vascular endothelial functions by helping maintain microcirculation in the kidney. Budding uninhibited by benzimidazole-1 (Bub1) plays a role in Akt and JNK signaling, which control TF and TM, respectively. We hypothesized that Bub1 could control vascular endothelial function in sepsis. The aim of this study was to determine the role of Bub1 in septic ARF. We used Mouse cecum ligation and puncture (CLP) using low Bub1 expressing ( Bub1 L/L ) and wild-type ( Bub1 +/+ ) mice in vivo and lipopolysaccharide (LPS) stimulation of human aortic endothelial cell (HAEC) in vitro . Bub1 L/L mice had a higher survival rate after CLP than Bub1 +/+ . Bub1 +/+ mice had more severe ARF after CLP than Bub1 L/L with blood biochemical and pathological analyses. TF expression in Bub1 +/+ mice and control HAEC (control) significantly increased in the septic model compared with Bub1 L/L and Bub1 silenced HAEC (siBub1). TM expression in the control significantly decreased after LPS stimulation compared with siBub1. Akt and JNK phosphorylation of siBub1 were attenuated after LPS stimulation. Associations of Bub1 with Akt or JNK after LPS stimulation of HAEC were detected using immunoprecipitation, suggesting that Bub1 is involved in the phosphorylation of Akt and JNK after LPS stimulation. Bub1 insufficiency attenuates TF expression and reduces TM suppression by blocking Akt and JNK phosphorylation, respectively, thus leading to the prevention of ARF and death caused by sepsis. Abstract : Supplemental Digital Content is available in the text